2013
DOI: 10.1186/1532-429x-15-87
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of left ventricular diastolic function by fractional area change using cine cardiovascular magnetic resonance: a feasibility study

Abstract: BackgroundEvaluation of left ventricular (LV) diastolic function is essential for the management of heart failure. We verified whether LV diastolic function could be evaluated by measuring the fractional area change (FAC) using cine cardiovascular magnetic resonance (CMR).MethodsWe collected clinical data from 59 patients who underwent echocardiography and cine CMR. Normal, impaired relaxation, pseudonormal, and restrictive LV filling were observed in 15, 28, 11, and 5 patients, respectively. We calculated FAC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 19 publications
0
16
0
2
Order By: Relevance
“…4) The LV volume change at 30% and 50% of the diastolic duration (defined as the temporal interval between T ESV to end of the R-R interval) normalized to stroke volume (SV) was defined as the diastolic index at 30% (DI 30% ) and 50% (DI 50% ), respectively. 26 5) EFP was defined as the temporal interval between ESV and the onset of atrial contraction (estimated from the dV/dt curve), and the LFP was defined as the interval between the onset and end of atrial contraction. 6) The peak early filling rate (R EFP ) and peak late filling rate (R LFP ) were identified as the peak positive volume rates during EFP and LFP, respectively (corresponding to E and A peaks in Doppler echocardiographic peak filling velocities during mitral inflow).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4) The LV volume change at 30% and 50% of the diastolic duration (defined as the temporal interval between T ESV to end of the R-R interval) normalized to stroke volume (SV) was defined as the diastolic index at 30% (DI 30% ) and 50% (DI 50% ), respectively. 26 5) EFP was defined as the temporal interval between ESV and the onset of atrial contraction (estimated from the dV/dt curve), and the LFP was defined as the interval between the onset and end of atrial contraction. 6) The peak early filling rate (R EFP ) and peak late filling rate (R LFP ) were identified as the peak positive volume rates during EFP and LFP, respectively (corresponding to E and A peaks in Doppler echocardiographic peak filling velocities during mitral inflow).…”
Section: Discussionmentioning
confidence: 99%
“…3) Isovolumic relaxation time (IVRT) was defined as the temporal interval between T ESV and the onset of rapid LV filling. 4) The LV volume change at 30% and 50% of the diastolic duration (defined as the temporal interval between T ESV to end of the R‐R interval) normalized to stroke volume (SV) was defined as the diastolic index at 30% (DI 30% ) and 50% (DI 50% ), respectively . 5) EFP was defined as the temporal interval between ESV and the onset of atrial contraction (estimated from the dV/dt curve), and the LFP was defined as the interval between the onset and end of atrial contraction.…”
Section: Methodsmentioning
confidence: 99%
“…Other MRI-based diastolic parameters have been proposed, including parameters obtained from flow patterns and tissue characterization (Ellims et al 2012;Okayama et al 2013;T€ oger et al 2016). Atrial tissue characterization has recently become feasible noninvasively using an MRI method for visualizing fibrosis as LA late gadolinium enhancement (LGE) (McGann et al 2008;Gatehouse et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that this approach allowed a reliable assessment of diastolic function in a mouse model of dilated cardiomyopathy at 4.7 T [47, 147] and the technique was further successfully used by other teams at higher field [1,17,174]. More recently, Buonincontri et al used a similar (simplified) approach derived from echocardiographic color kinesis (Echo-CK), to measure diastolic index in a mouse model of diabetes ([30], at 4.7 T), a concept previously described and validated in humans [113]. Ideally, these measurements require acquisitions with high temporal resolution (C20 phases), to improve their reliability.…”
Section: Evaluation Of Cardiac Volumes Mass and Functionmentioning
confidence: 99%